The Effect of Cutting Speed on the Machinability During Drilling D2 Hardened Steel - Md Noor, Muhammad Aimran (IRC, 2017)
This paper describe an experimental investigation on the effect of cutting speed on difficult-to cut-material, D2 hardened steel under drilling process. 6 sets of experiments were conducted using carbide drill bits with two different drilling diameters (3mm and 6mm) and three cutting speeds (15m/min, 25m/min and 35m/min). In addition, metal removal rate, surface roughness, final diameter, tool wear and chip morphology are the expected results for the project.